Strengthening Student Values and Morals Through the Application of Philosophy Into Islamic Education - Fadzila Binti Rahman; Miftachul Huda (Fakultas Agama Islam Universitas Billfath, 2023)
Success in Islamic Education means the ability to produce congregant who understands the essence of purification of feelings (takhalli) that is free from immoral behavior molded by commendable morals (tahalli). Therefore, moral education should be the mainstay of the development of the soul in order to spiritually instill individuals who are aware of their responsibilities in Islamic teaching. This study aims to identify the relevancy and the role of Islamic philosophy in strengthening moral values. This study was conducted using bibliographic methods through literature highlights as a reference for the study. In completing this article, the writer integrates monotheism, Islamic philosophy, and values needed to be improved. In addition, re-evaluation of the existing education system from all aspects is recommended to ensure the education system implemented follows the Qur'an and the Sunnah of the Prophet (PBWH) hopes and aspirations